Tensions in understanding inclusive education: conceptual and practical dilemmas - Ocampo González, Aldo (Escuela Profesional de Ciencias de la Comunicación Social de la Universidad Nacional del Altiplano, 2021)
This paper analyzes the building blocks of the rationality system of inclusive education, confirming that its application to teacher training and public policies establish categories through which they are placed tactically at the service of power. Each of these is used to speak for specific purposes, leading to the legitimization of an innocent fraud in which inclusive education approaches are cross-dressed with the force of the special, giving itself a benign and potentially new face that does not undo the problems introduced by the neoliberal educational imagination. Its objective is to critically analyze the impacts that arise from the lack of epistemic-conceptual and methodological clarity that inclusive education faces in the management of public policies and teacher training and their transfer to educational communities. The methodology used in this work was that of critical documentary review. It concludes, stating that inclusive education addresses issues related to the nature of exclusion, justice and educational transformation and the problem that designate the ownership of human rights in the school experience in the absence of ethical and social responsibility of educational systems.